2014
DOI: 10.5588/pha.14.0069
|View full text |Cite
|
Sign up to set email alerts
|

High time to use rapid tests to detect multidrug resistance in sputum smear-negative tuberculosis in Belarus

Abstract: Eastern Europe is facing an epidemic of multidrug-resistant tuberculosis (MDR-TB). 1,2 Belarus is one of the 27 high MDR-TB burden countries designated by the World Health Organization (WHO). A countrywide survey conducted in 2011 in Belarus revealed a prevalence of MDR-TB of 32% among new and 76% among previously treated TB cases, the highest documented rates worldwide. 3,4 However, these levels were found among sputum smear-positive pulmonary TB (SP-PTB) patients. The levels of MDR-TB among smear-negative pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Our study showed higher SNMDR TB prevalence in comparison with a study in Iran among tuberculosis patients in between the year 2011–2013, which was 4.3% (2.38% in the new TB treatment group and 23.1% in the retreatment groups) [35]. The present study demonstrated low MDR TB prevalence as compared to a finding by a study in Belarus which was 47% SNMDR-TB: 33% among new and 73% among previously treated patients [15]. But, our study showed high prevalence of SNMDR TB in comparison with a study in India that was conducted among newly diagnosed sputum-positive pulmonary tuberculosis between February 2008 and December 2009 demonstrated very low prevalence that was 1.13% MDR-TB [36].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Our study showed higher SNMDR TB prevalence in comparison with a study in Iran among tuberculosis patients in between the year 2011–2013, which was 4.3% (2.38% in the new TB treatment group and 23.1% in the retreatment groups) [35]. The present study demonstrated low MDR TB prevalence as compared to a finding by a study in Belarus which was 47% SNMDR-TB: 33% among new and 73% among previously treated patients [15]. But, our study showed high prevalence of SNMDR TB in comparison with a study in India that was conducted among newly diagnosed sputum-positive pulmonary tuberculosis between February 2008 and December 2009 demonstrated very low prevalence that was 1.13% MDR-TB [36].…”
Section: Discussionsupporting
confidence: 45%
“…Smear negative pulmonary TB (SNPT) is a critical clinical and public health problem [11, 12]. This SNPT prevalence can reach 36 to 45% in United States of America [13], 65.2% in Brazil among high HIV prevalence setting (41.1%) [9], 68.1% in Italy [14], 55% in Belarus (from this 47% were smear negative MDR TB) [15]. Studies in Ethiopia have shown different evidences of SNPT prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…MDR phenotype or mono-resistance to INH or rifampicin was observed in an alarming proportion of our patients (12.4% of the recruited participants and 47.4% of the culture-positive participants). Previous studies have reported a varying range (10.8-50%) 18,19 of anti-tubercular drug resistance among sputum smear-negative participants. A wide variety of factors, including the endemicity of drug-resistant strains, the proportion of relapse and chronic cases, treatment defaulters and HIV-TB co-infected patients in the study group, and the TB prescription practices and compliance trends in the community can lead to a variable proportion of drug resistance in different studies.…”
Section: Discussionmentioning
confidence: 98%
“…A study from Belarus performed in 2009 identified positive association between disability and MDR/RR-TB prevalence [ 35 ]. Concerning another type of social security policies, influence of retirement social status on the risk of MDR/RR-TB development is uncertain as both positive and negative relationships were reported in the literature [ 13 , 36 ]. A study conducted in Ethiopia revealed a tenfold increase in risk of MDR-TB for the military pensioners, explaining it as pensioners receive much fewer social benefits compared to the active military servicemen [ 13 ].…”
Section: Discussionmentioning
confidence: 99%